PENGARUH TEKNIK BLEEDING DAN JENIS MEDIA PENDINGIN TERHADAP MUTU FILLET IKAN KAKAP PUTIH(Lates calcarifer Bloch) - I Gede Widi Sedana; I Wayan Widia; Ni Luh Yulianti (Jurnal BETA (Biosistem dan Teknik Pertanian), 2015)
The aimed of this research were to determine the effect of bleeding techniques and types of cooling mediumon the fillet’s quality of Barramundi (Lates calcalifer Bloch). Experimental design with two factors, namely bleeding technique factor and cooling medium factor was used on this research. Bleeding techniques consist of four treatments, i.e without bleeding, one wounded, two wounded, and ike-jime. Types of cooling medium factor consists of four treatments, i.e without media, cold water, ice flake, and ice slurry. Observed variables were visual, aroma, texture, temperature, pH, TPC, and TVB. The results showed that bleeding techniques and the types of cooling medium affected the fillet’s quality of Barramundi significantly. The interaction between two wounded bleeding technique and ice slurry cooling media showed the best result with the value of aroma,texture, pH, TVB, and TPC quality indicator was 5.6 (rather fresh), 7.07 (fresh), 7.34 (fresh), 6.42, 4.74 mg N/100 g, 4.30x10^3 colony/g, respectively.